THE INTERNET OF THINGS: LIMITLESS OPPORTUNITIES FOR BUSINESS AND SOCIETY - Attaran, Ph.D., Mohsen (Journal of Strategic Innovation and Sustainability, 2017)
The World Wide Web created a connection from computers to networks. The next evolution that followed connected people to the Internet and to other people. The Internet of Things (IoT) is emerging as the third wave in the development of the Internet. IoT interconnects devices, people, environments, virtual objects, and machines. IoT is expected to revolutionize and change the way all businesses, governments, and consumers interact with the physical world. In the exploding world of IoT, there is much to learn and an overwhelming amount of research to be done. The objective of this paper is to go beyond the hype and explore basic issues related to IoT technology, including its promises as well as its pitfalls. This study discusses potential strategic benefits of this technology as well as its risks and limitations. It highlights its evolving technologies and trends and their impact on the world of tomorrow. Also, it reviews IoT’s potential economic impact and explores many factors that may contribute to its successful adoption and deployment. Finally, this study explores IoT’s potential application in various industries